Reverse influence of riparian buffer width on herbivorous and predatory Hemiptera. (8th September 2014) - Gilbert, S.; Norrdahl, K.; Tuomisto, H.; Söderman, G.; Rinne, V.; Huusela‐Veistola, E.
Abstract Insects are major contributors to farmland biodiversity, and their economic roles are also diverse. Many herbivorous species are crop pests, while predatory insects have the potential to act as biological controls against pests. Overall insect diversity has declined as a result of intensified agricultural practices. Riparian buffers may support insect populations in intensively cultivated areas, but their actual impact on the balance between harmful pests and beneficial predators is not known. It can be postulated that this impact may vary depending on the characteristics and location of the riparian buffer itself. We investigated the possibility that the biotic and abiotic attributes of agricultural riparian buffers adjoining crop fields and watercourses can explain the species composition of hemipteran assemblages. In particular, we were interested in the abundances of species belonging to the genus Nabis (generalist predators) and recognized and potential pests of cereal crops. Riparian buffer width and the presence or absence of woody plants were not associated with hemipteran species turnover among riparian buffers. In contrast, differences in the degree of dominance by grasses, in plant species turnover, and in which crop plant was cultivated in the adjacent field, explained a significant proportion of the variance in hemipteran species turnover. The abundance of predatory Nabis species increased with increasing riparian buffer width, whereas the abundance of recognized and potential crop pests decreased. The reverse patterns in the predatory and herbivorous Heteroptera suggest that increasing riparian buffer width might enhance biological control by Nabis predators.